Protective roles and protective mechanisms of neutralizing antibodies against SARS-CoV-2 infection and their potential clinical implications - Abebe, Endeshaw Chekol; Dejenie, Tadesse Asmamaw (Frontiers in Immunology, 2023)
Neutralizing antibodies (NAbs) are central players in the humoral immunity that defends the body from SARS-CoV-2 infection by blocking viral entry into host cells and neutralizing their biological effects. Even though NAbs primarily work by neutralizing viral antigens, on some occasions, they may also combat the SARS-CoV-2 virus escaping neutralization by employing several effector mechanisms in collaboration with immune cells like natural killer (NK) cells and phagocytes. Besides their prophylactic and therapeutic roles, antibodies can be used for COVID-19 diagnosis, severity evaluation, and prognosis assessment in clinical practice. Furthermore, the measurement of NAbs could have key implications in determining individual or herd immunity against SARS-CoV-2, vaccine effectiveness, and duration of the humoral protective response, as well as aiding in the selection of suitable individuals who can donate convalescent plasma to treat infected people. Despite all these clinical applications of NAbs, using them in clinical settings can present some challenges. This review discusses the protective functions, possible protective mechanisms against SARS-CoV-2, and potential clinical applications of NAbs in COVID-19. This article also highlights the possible challenges and solutions associated with COVID-19 antibody-based prophylaxis, therapy, and vaccination.